2004
DOI: 10.1111/j.1365-3121.2004.00531.x
|View full text |Cite
|
Sign up to set email alerts
|

SHRIMP U–Pb zircon dating of quartz‐bearing eclogite from the Sanbagawa Belt, south‐west Japan: implications for metamorphic evolution of subducted protolith

Abstract: In order to decipher the origin of eclogite in the high‐P/T Sanbagawa metamorphic belt, SHRIMP U–Pb ages of zircons from quartz‐bearing eclogite and associated quartz‐rich rock (metasandstone) were determined. One zircon core of the quartz‐rich rock yields an extremely old provenance age of 1899 ± 79 Ma, suggesting that the core is of detrital origin. Eight other core ages are in the 148–134 Ma range, and are older than the estimated age for trench sedimentation as indicated by the youngest radiolarian fossil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
98
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(103 citation statements)
references
References 34 publications
5
98
0
Order By: Relevance
“…The temperature of the Sambagawa metamorphism (600°C) is lower than the closure temperature of the garnet, and consequently the isotopic re-equilibrium of the Sm-Nd system in the whole Nikubuchi complex during the Sambagawa metamorphism is unlikely. Okamoto et al (2004) reported the U-Pb ages of metamorphic zircon rims (112-132 Ma) from the quartz-bearing eclogite, and these ages are consistent with the peak age of the Sambagawa metamorphism (100-120 Ma). They also reported the zircon core ages (134-148 Ma), which provide a maximum deposition age for the sandstones of the SMB.…”
Section: The Meaning Of the Sm-nd Whole-rock Isochron Age And Origin supporting
confidence: 58%
See 1 more Smart Citation
“…The temperature of the Sambagawa metamorphism (600°C) is lower than the closure temperature of the garnet, and consequently the isotopic re-equilibrium of the Sm-Nd system in the whole Nikubuchi complex during the Sambagawa metamorphism is unlikely. Okamoto et al (2004) reported the U-Pb ages of metamorphic zircon rims (112-132 Ma) from the quartz-bearing eclogite, and these ages are consistent with the peak age of the Sambagawa metamorphism (100-120 Ma). They also reported the zircon core ages (134-148 Ma), which provide a maximum deposition age for the sandstones of the SMB.…”
Section: The Meaning Of the Sm-nd Whole-rock Isochron Age And Origin supporting
confidence: 58%
“…The Besshi unit is dominated by pelitic, basic, and siliceous schists. The metamorphic age of the unit is considered to be Late Cretaceous (100-120 Ma) on the basis of a Rb-Sr wholerock isochron age of 116 ± 10 Ma for pelitic schists (Minamishin et al, 1979), U-Pb ages ranging from 112 to 132 Ma on overgrown parts of zircons in quartz eclogite (Okamoto et al, 2004), the 40 Ar/ 39 Ar whole-rock ages of schists that range between 85 and 94 Ma (Takasu and Dallmeyer, 1990) and the muscovite K-Ar age of schists, which range from 65 to 90 Ma (Itaya and Takasugi, 1988).…”
Section: Geological Setting and Samplesmentioning
confidence: 99%
“…In addition, Narita et al (1999) suggested that the age of the Kuma Group (Hiwada -toge Formation) was dated Early Eocene. And zircon ages of eclogite support that the age of peak metamorphism was 120 -110 Ma (Okamoto et al, 2004). Although most of the above results were based on the research conducted on Shikoku Island, it was assumed that the belt on the Kanto Mountains has a similar history.…”
Section: Introductionmentioning
confidence: 91%
“…3). Okamoto et al (2004) reported SHRIMP U Pb ages of 1899 ± 79 Ma and 148 134 Ma for the detrital core and 132 112 Ma for the metamorphic rim of zircon grains from the quartz eclogite samples, and interpreted that the eclogite facies metamorphism peaked at 120 110 Ma. The trend of bulk rock compositions and the presence of detrital zircon grains suggest that the protolith of the quartz eclogite is a sedimentary mixture of pelitic and basic volcaniclastic materials as proposed by Takasu (1989).…”
Section: Geological Outline and Petrographymentioning
confidence: 99%